Eficácia do laser de baixa potência na redução das morbidades causadas pela exodontia de terceiros molares: ensaio clínico triplo-cego de boca dividida - Nunes, Carlos Eduardo Nogueira (2022)
It is known that the use of low power laser (LPL) has different effects in modulating the inflammatory process. At the same time, third molar extraction can bring related morbidities to patients, with pain, trismus and edema being the main ones. Therefore, a discussion about the effectiveness of the use of protocol the LPL in reducing such morbidities is opened. The aim of this clinical research is to evaluate the effectiveness of the use of LPL in reducing pain, trismus and edema after impacted lower third molar extraction. A split-mouth randomized triple-blind clinical trial (patient, surgeon and statistician without knowledge of group allocation) was conducted at the dentistry clinic of the Federal University of Ceará - Campus Sobral with patients who sought the service with the need for third-party extraction lower molars. Patient eligibility criteria, as well as surgical and data collection protocols were strictly followed in order to reduce biases during the conduct of the research. Each patient had a need for two surgical procedures for extraction of the lower third molars (38 and 48), with these procedures being randomly allocated into two groups, with the test group (TG) being the one that went with the LPL application protocol and the placebo group (PG) that completes the simulation of the application of the LPL. The collection of initial parameters and the surgical procedure, followed with the collection of all immediate postoperative data, postoperative period of 48 hours and 7 days. At the end of collection, statistical analysis performed using the SPSS program and reference tests. Final sample consisted of 22 patients and 44 surgeries. TG patients used, on average, half the amount of analgesics that the GP used (GT:2.00 and GP:4.04) and it was statistically significant on days four and five. The TG had lower numbers on the visual numerical scale (VNS) compared to the GP (GT:3.81 and GP:4.40) but with no statistically significant difference. The GT showed better indicators both after 48 hours (48H) and after 7 days (7D) of surgery than the GP when trismus was evaluated (GT48H:-9.41mm; GT7D:5.50mm and GP48H:13.31mm; GP7D :9.22mm), but with no statistically significant difference. Regarding edema, GP and GT do not show significant differences. Thus, in the current research, the use of LBP presented better indicators for pain and trismus reduction after third molar extraction. Therefore, the use of LBP is safe and indicated as an auxiliary therapy in the treatment of morbidities after tooth extractions.